Barriers to implementing childbirth recommendations in Brazil: the women's perspective - Ávila Teixeira Vidal; Jorge Otávio Maia Barreto; Daphne Rattner (Pan American Health Organization, 2021)
Objective. To identify barriers to the implementation of National Childbirth Guidelines in Brazil from the women's perspective. Methods. A descriptive exploratory study was performed using a qualitative approach and an interpretive perspective. The hermeneutic unit of analysis was established based on the contribution of users to a public online consultation about the National Childbirth Guidelines in Brazil, performed in 2016 by the National Committee for Health Technology Incorporation into the Unified Health System (CONITEC). Content analysis techniques were used to examine the answers provided to the following specific question: "Considering your local reality, what would hinder the implementation of this protocol or guideline?" Results. Of 396 contributions recorded by CONITEC, 55 were included in the content analysis. The mean age of women was 31 years, with most self-declared as white (69%) and living in the Southeast of Brazil (56.3%). Coding revealed seven barrier categories, which were grouped into three families - barriers related to 1) professional training and culture (which highlighted the centrality of physicians, not women, in childbirth), 2) social culture (general population not well informed), and 3) political and management issues (little interest on the part of managers, lower physician compensation for vaginal childbirth vs. cesarian section, and poor hospital infrastructure). Conclusions. Aspects of professional training and culture, social culture, and political as well as management issues are critical points to be considered in future interventions aiming at overcoming or weakening the barriers to implementing childbirth recommendations in Brazil.